Hyperbaric Oxygen Therapy for Diabetic Foot Ulcers in Sub‐Saharan Africa: A Critical Review of Clinical Evidence, Health‐System Feasibility and Public Health Implications - Matthew Chibunna Igwe; Esther Ugo Alum; Alphonsus Ogbonna Ogbuabor; Yibala Ibor Oboma; Onyinyechi Bede‐Ojimadu; Charles Iyore Idehen (International Wound Journal, 2026)
ABSTRACT Diabetic foot ulcers are an important cause of morbidity, amputation, disability and healthcare expenditure in sub‐Saharan Africa, where limitations in preventive foot care, referral pathways, vascular services, multidisciplinary wound care and financial protection may contribute to poor outcomes. This critical narrative review evaluates the potential role of systemic hyperbaric oxygen therapy as an adjunct to standard diabetic foot ulcer care in sub‐Saharan Africa by integrating evidence on clinical effectiveness and safety with health‐system, economic, equity and implementation considerations. Evidence was drawn from clinical studies, systematic reviews, clinical guidelines, economic evaluations and literature relevant to diabetic foot care and health‐system capacity in the region. Global evidence suggests that systemic hyperbaric oxygen therapy may improve wound healing in selected patients whose ulcers fail to heal with best standard care, but findings remain heterogeneous; evidence for reducing amputation is uncertain, and direct regional evidence is sparse. Implementation in sub‐Saharan Africa would require reliable oxygen, electricity, trained staff, safe maintenance systems, multidisciplinary care, referral pathways, sustainable financing and feasible treatment completion. The therapy should therefore not be considered routine or first‐line treatment. Where appropriate infrastructure exists, carefully monitored referral‐centre pilots should assess clinical outcomes, safety, treatment completion, affordability, budget impact and equity before wider implementation.